2014
DOI: 10.4103/0019-5413.132533
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Candida arthritis

Abstract: Fungal arthritis is an uncommon yet serious disorder in the newborn. Delay in diagnosis and management can lead to significant morbidity. We report our experience with management of two such cases. Two preterm neonates with multifocal arthritis caused by Candida were studied. Diagnosis was made by clinical examination, laboratory investigations, radiological investigations and culture. Both were treated by aspiration, arthrotomy and antifungal therapy. One patient recovered fully from the infection while the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Deshpande et al observed similar negative cultures rates in their patients [18] although they noticed only 7% fungal infections. However, it has been observed that the rates of fungal septic arthritis are increasing over a period of time due to rampant use of antibiotics [19] . Other organisms isolated from the pus specimens were most commonly gram negative Klebsiella (24.2%) and E. Coli 6 (6.6%) followed by S. aureus 6 (6.6%) and MRSA 4(4.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deshpande et al observed similar negative cultures rates in their patients [18] although they noticed only 7% fungal infections. However, it has been observed that the rates of fungal septic arthritis are increasing over a period of time due to rampant use of antibiotics [19] . Other organisms isolated from the pus specimens were most commonly gram negative Klebsiella (24.2%) and E. Coli 6 (6.6%) followed by S. aureus 6 (6.6%) and MRSA 4(4.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Other organisms isolated from the pus specimens were most commonly gram negative Klebsiella (24.2%) and E. Coli 6 (6.6%) followed by S. aureus 6 (6.6%) and MRSA 4(4.4%). It has been observed that in the recent past gram negative organisms have replaced gram positive organisms as the most common cause of septic arthritis [19] . Besides, the type of organism isolated from the specimen depends upon the type of hospital, local dominant flora and patient characteristics (gestational age, birth weight, postnatal age, associated conditions) [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the type of organism isolated from the specimen depends upon the type of hospital, local dominant ora and patient characteristics (gestational age, birth weight, postnatal age, associated conditions. 16 e coexistence of osteomyelitis and septic arthritis in the newborn population is higher than in pediatric age group.…”
Section: Figure-2: Prognosis According To Mode Of Treatment (N=30)mentioning
confidence: 98%